Biomarkers for Bronchopulmonary Dysplasia in the Preterm Infant - Rivera, Lidys; Siddaiah, Roopa; Oji-Mmuo, Christiana; Silveyra, Gabriela R.; Silveyra, Patricia (Frontiers in Pediatrics, 2016)
Bronchopulmonary dysplasia (BPD) is a chronic inflammatory lung disease of very low birth weight (VLBW) preterm infants, associated with arrested lung development and a need for supplemental oxygen. Over the past few decades, the incidence of BPD has significantly raised as a result of improved survival of VLBW infants requiring mechanical ventilation. While early disease detection is critical to prevent chronic lung remodeling and complications later in life, BPD is often difficult to diagnose and prevent due to the lack of good biomarkers for identification of infants at risk, and overlapping symptoms with other diseases such as pulmonary hypertension (PH). Due to the current lack of effective treatment available for BPD and PH, research is currently focused on primary prevention strategies, and identification of biomarkers for early diagnosis, that could also represent potential therapeutic targets. In addition, novel histopathological, biochemical, and molecular factors have been identified in the lung tissue and in biological fluids of BPD and PH patients that could associate with the disease phenotype. In this review, we provide an overview of biomarkers for pediatric BPD and PH that have been identified in clinical studies using various biological fluids. We also present a brief summary of the information available on current strategies and guidelines to prevent and diagnose BPD and PH, as well as their pathophysiology, risk factors, and experimental therapies currently available.